(untitled) (Journal of Environmental Science and Natural Resources, 2015)
To investigate the response of mineral phosphatic fertilizer and inoculum alone or integrated use of these sources on the growth, yield, nutrient uptake and phosphorus use efficiency of wheat. Treatment combinations were: T0=Control, T1= Pseudomonas sp, T2= Klebsiella sp, T3= Pseudomonas sp + 15 kg P ha-1, T4= Klebsiella sp + 15 kg P ha-1 and T5= 30 kg P ha-1. Trials were laid out in a randomized block design with four replications having unit plot size of 5 m × 3 m and wheat was the test crop. Maximum grain and straw yield (2.13 and 2.84 t ha-1) were recorded in T3 (PSB 7 + 15 kg P ha-1) and T4 (PSB 19 + 15 kg P ha-1) treatments at Pabna and Rajshahi, respectively. Pseudomonas sp for Pabna and Klebsiella sp for Rajshahi along with triple super phosphate showed better performance than other treatments in respect of wheat yield, nutrient uptake and quality of soil. Phosphate solubilizing bacteria alone also increased phosphorus use efficiency during crop production. A positive significant correlation was observed between yield contributing characters and grain yield of wheat. Based on these reults it may be concluded that, phosphate solubilizing bacteria contributed from unavailable to available form of soil phosphorus and stimulated the available form of applied phosphatic fertilizer as a result increased nutrient uptake and yield of wheat. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22148 J. Environ. Sci. & Natural Resources, 7(1): 75-79 2014